Legal Transplantation to the Muslim World: A Case Study of the Iraqi Civil Code under the Auspices of al-Sanhūrī's Legal Approaches - Ammar Kareim Kadham al-Bsherawy; Kasim Hayaal Resan al-Obaidi (پژوهش‌نامه حقوق اسلامی)
"Legal Transplantation," the process of transferring a rule or legal system from one country to another, is a concept introduced by Scottish legal scholar Alan Watson in the 1970s. Legal scholars hold diverse opinions on legal transplantation, with some advocating for it and others opposing it, each providing evidence to support their stance. The Iraqi civil law incorporated legal transplantation through the efforts of the esteemed jurist Abd al-Razzāq al-Sanhūrī. However, al-Sanhūrī's transplantations did not achieve the expected success in all instances. In several key areas, the transplantations did not function as anticipated and remain underutilized. This paper investigates the failures of legal transplantation by examining two specific examples: the foundation system and the consensual subrogation system. The primary reason for the unsuccessful transplantation in Iraqi civil law is the lack of originality in the transplanted material when compared to the originality and comprehensiveness of Islamic jurisprudence.